Small interfering RNA-mediated control of virus replication in the CNS is therapeutic and enables natural immunity to West Nile virus - Beloor, Jagadish (Cell Host Microbe, 2018)
No vaccines or therapeutics are licensed for West Nile virus (WNV), a mosquito-transmitted neuroencephalitic flavivirus. The siRNA, siFvE(JW), targets a conserved sequence within the WNV E protein and limits virus infection. Using a Rabies virus-derived neuron-targeting peptide (RVG9R) and an intranasal route for delivering siFvE(JW) to the CNS, we demonstrate that treatment of WNV-infected mice at late stages of neuroinvasive disease results in recovery. Selectively targeting virus in the CNS lowers viral burdens in the brain, reduces neuropathology, and results in a 90% survival rate at 5-6 days post-infection (when viral titers peak in the CNS), while placebo-treated mice succumb by day 9-10. Importantly, CNS virus clearance is achieved by humoral and cell-mediated immune responses to WNV infection in peripheral tissues, which also engender sterilizing immunity against subsequent WNV infection. These results indicate that intranasal RVG9R-siRNA treatment offers efficient late-stage therapy and facilitates natural long-term immunity against neuroinvasive flaviviruses.